Manta térmica para telhados a base de bucha vegetal (luffa cylindrica): uma proposta eco sustentável - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
In recent decades, the world consumption of products has increased significantly, as a result, industrialization is driven to meet this demand, generating environmental impacts. It is necessary to seek sustainable alternatives to replace marketed products whose origin comes from non-renewable sources. The thermal blanket is used in roof structures, whose use necessarily promotes greater thermal comfort, and currently does not have an alternative of natural origin. The objective of this research is to test the vegetal loofah (Luffa Cilíndrica), an ecologically sustainable product that presents ecological sustainability, as it is a known natural fiber and that has relevant production in the Amazon region, as a thermal blanket to promote thermal comfort in buildings. Six boxes of identical size and materials were prepared (test cells) where there would be differentiation only in the blanket used under the roof, one without a blanket (matrix cell), one with a fiberglass blanket, one with a reflective aluminum blanket and three cells with progressive loofah load (300g/m2, 600g/m2 and 900g/m2), these in order to analyze the performance by material density. The cells were positioned outdoors, at the Centro Universitário Luterano de Santarém (CEULS∕ULBRA), their internal temperature was collected every three hours from thermocouples and a CR10 datalogger, for the measurement of the local temperature, INMET data were collected, ANOVA statistical analysis was adopted with application of Turkey's test. It was verified that the cells with a load of vegetable loofah had a similar performance to the matrix cell and the cell with an aluminum blanket load, proving to be sufficient to be used as a thermal blanket in buildings. Therefore, it was concluded that the use of the Luffa C. blanket can be an adequate substitute for the currently commercialized blankets.
Keywords: Bucha vegetal; Luffa cylindrica; Telhados residenciais; Produto ecologicamente sustentável; CNPQ::CIÊNCIAS BIOLÓGICAS; Estudos e Manejos dos ecossistemas amazônicos